A mix methodology study to compile the factors contributing towards poor uptake of antiretroviral therapy among high-risk groups: Female sex workers, people with intravenous drug use on opiod substitution therapy - Debjani Sengupta; Archi Chandra; Upasana Poddar; Rahul Biswas; Pramit Ghosh; Arkaprovo Pal; Sandipta Chakraborty; Debjani Guchait (Journal of Family Medicine and Primary Care)
Background: Biobehavioral surveys confirm that HIV prevalence is high or ‘concentrated’ among ‘key populations’ (KPs) who have unprotected sexual contacts with multiple partners or who engage in injecting drug use. These populations include female sex workers (FSW), men who have sex with men (MSM), hijra/transgender (TG), and people who inject drugs (PWID). Antiretroviral therapy is offered under the program of National AIDS Control to Seropositive population at the designated center. Other than the stigma of being HIV positive, there is an additional factor present among these groups of people hindering their uptake of antiretroviral therapy. Aims: To identify and quantify the factors causing poor uptake of ART (antiretroviral therapy) among high risk group of subjects receiving antiretroviral therapy, namely, female sex workers (FEW) and intravenous drug users (IDU). A concurrent parallel design of mixed methodology was conducted with integration of the two arms at analysis. Material and Method: The quantitative arm involves a retrospective cohort analysis of group on ART having “exposure” defined as high risk behavior for a period of 1 year. High-risk behavior constituted of exposure involved in commercial sex work and those exposed to intravenous drug usage. The comparator arm was sex-matched cohort who were sero-positive and on ART but did not have an “exposure” to defined high-risk behavior practice for a period of 1 year. The qualitative arm constituted of development of a grounded theory based on thematic analysis from coded transcripts. Result: Time taken to travel and expenditure incurred therein added with long waiting time compounded with loss of daily wage (reiterated in both arms) emerged to be the most prominent factor. Conclusion: Monetary incentive for travel, single window service rapid service and process to access drugs from any center (via a central registration system if possible) may be useful.